"For We ascend in holiness and do not descend." Jewish ultra-Orthodox women's agency through their discourse about media. Issue 2 (3rd April 2019) - Neriya-Ben Shahar, Rivka
ABSTRACT: "Permission" and "prohibition" are key terms in Jewish religious discourse. For generations they have dominated as part of the primarily male, rabbinic discourse in talmudic literature. This paper will show that men no longer hold the monopoly on these terms because contemporary Israeli ultra-Orthodox women include them in their daily conversation in multiple and varied ways. The study examines exposure patterns and perceptions of 42 ultra-Orthodox women toward sectarian and general mass media. In responses to detailed questionnaires, the words "prohibited, " "forbidden" and "a boundary" constantly recur along with a variety of negatives, such as "not permitted, " "not allowed" and "not kosher". This paper argues that in describing their uses of and perceptions toward mass media, ultra-Orthodox women have adopted terminology borrowed from what was previously a primarily male-dominated conversation. Some might argue that these women are simply working within the bounds of ultra-Orthodox law which they accept as universally applicable; or perhaps that these women are simply reflecting words used by their husbands or rabbis. However, this study argues that their adoption of these terms indicates they are exercising their own agency. With a combined religious and secular education, and work that is primarily outside the house, many of them are the principal breadwinners in their homes. I suggest that this discourse is a part of their highly intelligent navigation of their simultaneous roles as both gatekeepers and change agents.